Research status and development direction of Child-Friendly Cities: a bibliometric analysis based on VOSviewer - Mingyue Yang; Taig Youn Cho; Xu Liu; Yuhang Dai (Journal of Asian Architecture and Building Engineering)
Since the introduction of The Child-Friendly Cities Initiative in 1996, there has been a growing body of research in this period. Many countries have made some attempts to create Child-Friendly Cities (CFC). However, there is yet to be a clear answer to how to create more child-friendly environments. Therefore, this study aims to analyze the current state of research on CFC through bibliometric analysis and to find future research directions by understanding the inadequacy of the current research. The study searched the database for all literature related to “CFC” from 1996 to 2023. After 166 documents were retrieved, they were analyzed for the overall trends in the number of articles published, main collaborating countries, main publishing journals, and keyword co-occurrence. The findings suggest that existing research has shifted from the broader concept of children’s environments to gradually focusing on the individual child. However, the underlying preferences of “children” as the primary users of space have yet to be explored. Also, the neurological mechanisms in the brain that influence the generation of positive emotions and brain development in children have yet to be mentioned. Accordingly, future research directions are proposed, providing a reference for research on creating CFC.